Analysis of Transjakarta Bus Rapid Transit Infrastructure Services on Customer Satisfaction Performance with Large-Scale Social Restrictions in DKI Jakarta - Sunandar Ali; Anjas Handayani; Mohammad Sobirin; Mohammad Erzal Audifikria (NAROTAMA UNIVERSITY, Indonesia)
Quality service is a form of service that are provided by service providers in order to meet the needs of its customers. However, the Covid-19 pandemics has affected the quality of services, including the service of BRT Trans Jakarta. This can have a serious impact if not handled properly and can reduced customer satisfaction with these services. The purpose of this study is to determine the dominant factors that influence the infrastructure services of the Trans Jakarta BRT, to determine the quality of service on customer satisfaction performance during the large-scale social restrictions in DKI Jakarta. The purpose of this study is to find out the dominant factors that influence the infrastructure services of the BRT Trans Jakarta and to determine the quality of service on customer satisfaction performance during the large-scale social restrictions in DKI Jakarta. The concept studies used in this research are service, infrastructure, service quality, and customer satisfaction. This study used quantitative approach along with CSI (Customer Satisfaction Index) method and analysis of the level of conformity of IPA (Importance - Performance Analysis), the sampling system used were incidental sampling with the BRT Trans Jakarta user analysis unit during the large-scale social restrictions in DKI Jakarta. The results showed that the customer satisfaction index for BRT Trans Jakarta infrastructure services during the PSBB was 75.54% for the CSI value and IPA value of 98.54%, and the customer satisfaction criteria were in the Satisfied category.